Post-translational regulation of the tumour suppressor IRF-1 - Garvin, Alexander (2010)
IRF-1 (Interferon Regulatory Factor 1) is a transcription factor first identified as a regulator of Interferon expression. Two decades after its discovery, IRF-1 has been shown to be involved in numerous other pathways including apoptosis, cell cycle regulation, DNA damage/repair, immune cell development and inflammation. Transcriptional regulation of IRF-1 by a number of external agents has been extensively studied, however almost nothing is known about the posttranslational regulation of IRF-1 activity. In this study IRF-1 is shown to be phosphorylated at Thr180 by GSK3β (Glycogen Synthase Kinase 3β). Phosphorylated Thr180 promotes interaction with the ubiquitin E3 ligase SCFFbxw7u, (Skp1-Cu11-Fbxw7α) which increases turnover of IRF-1 protein. Phosphorylation dependent ubiquitination of IRF-1 was confirmed, as substitution of Thr180 to alanine reduced IRF-1 ubiquitination and increased stability. Enhanced phosphorylation of IRF-1 (by increasing GSK3β expression) promotes increased ubiquitination/degradation. Transactivation of the TRAIL (TNFα Related Apoptosis Inducing Ligand) promoter by IRF-1 was found to be dependent on GSK3β phosphorylation of Thr180 by use of reporter assays and inducible expression of IRF-1 in breast cancer cell lines. Importantly IRF-1 activity on the TRAIL promoter is dependent on proper turnover by the UPS (Ubiquitin Proteasome System), as chemical inhibition of the proteasome, or reduction in IRF-1 ubiquitination reduced activity in reporter assays. This suggests that phosphorylation of IRF-1 by GSK3β acts as a destruction signal through association with SCFFbxw7a. This signal dependent turnover of IRF-1 is required for proper transcriptional activation of the TRAIL promoter.